Evaluating language policy implementation in South African higher education - three decades of progress and challenges: A scoping review protocol - Silingene Joyce Ngcobo; Tracy Zhandire; Zamasomi Meyiwa Luvuno; Wilbroda Hlolisile Chiya; Celenkosini Thembelenkosini Nxumalo; Gugulethu Brightness Mazibuko; Busisiwe Purity Ncama; Sinegugu Evidence Duma; Deshini Naidoo (PLoS ONE, 2025)
Background South Africa’s higher education institutions (HEIs) continue to face challenges in implementing inclusive language policies that integrate indigenous African languages into academic settings, even three decades after apartheid. Higher Education Institutions (HEIs) face significant challenges in integrating indigenous African languages into academic settings. Despite progressive reforms, higher education institutions face significant challenges in integrating indigenous African languages into academic settings. Objectives This scoping review aims to evaluate the current state of language policy implementation in South African public HEis. Specifically, it seeks to: (1) map the integration of multilingual policies into teaching, research, and administrative practices; (2) identify persistent barriers to effective policy implementation; (3) explore successful strategies for promoting multilingualism (4) assess the extent of African language usage in academic contexts; and (5) identify research gaps to guide future investigations. Methods The review will adhere to the PRISMA-ScR guidelines and follow the framework outlined by Arksey and O’Malley, ensuring a systematic and transparent approach. A comprehensive search will be conducted in databases including Google Scholar, Scopus, Web of Science, ERIC, and African Journals Online (AJOL), covering studies published from 1994 to the present. This will be supplemented by grey literature from government and institutional sources. Three independent reviewers will screen studies using predefined eligibility criteria, managing and screening articles through Rayyan. Data will be extracted using a standardized form, and thematic analysis will synthesize the findings, with stakeholder consultation to validate results. Expected outcomes This review will provide a comprehensive assessment of language policy implementation, highlighting successful strategies and persistent challenges across institutions. The findings will inform policy refinement, identify effective practices, and guide future research directions for achieving linguistically inclusive higher education in South Africa, while contributing to a broader understanding of implementing multilingual policies in post-colonial educational contexts. This protocol is preregistered on OSF, available at https://doi.org/10.17605/OSF.IO/AU2SD